Dermoscopy of borderline tuberculoid leprosy. (22nd August 2017) - Ankad, Balachandra S.; Sakhare, Punit S.
Abstract: Introduction: Leprosy is a chronic granulomatous condition caused by Mycobacterium leprae, and borderline tuberculoid (BT) leprosy is the most common type of leprosy and presents with large, well‐ to ill‐defined hypopigmented patches. It is known for atypical presentations. Dermoscopy of granulomatous conditions is well documented. However, there is no description of dermoscopy of BT leprosy in the literature. Authors evaluated the dermoscopic patterns of BT leprosy. Case report: Patients with BT leprosy were studied for dermoscopic patterns. A total of 12 patients (8 male, 4 female) with a median age of 25 years were present. Mean duration of disease was 6 months. The most frequent pattern was white areas (100%) followed by decreased density of hairs. Yellow globules were observed in 8 (66.66%) patients. Decreased white dots (represent sweat duct openings) and branching vessels were noted in 6 (50%) and 4 (33.33%) patients, respectively. Conclusion: This is the first report of dermoscopy of BT leprosy in the literature, and new dermoscopic observations were made by the authors. Dermoscopy of BT leprosy shows characteristic patterns, thus it adds valuable information for the diagnosis of BT leprosy.